حوكمة صندوق الحج الماليزي (تابونغ حاجي): دراسة وصفية تحليلية: Governance of the Malaysian Hajj Fund (Tabung Haji): A Descriptive and Analytical Study - Shkar Hama Agha Qader; Abdulmajid Obaid Hasan Saleh; Mohamad Sabri B Zakaria (International Journal of Al-Turath In Islamic Wealth and Finance, 2024)
الملخص يُسلّط هذا البحث الضوء على أهمية تطبيق الحوكمة في المؤسسات المالية الإسلامية، التي تتميز بخصوصيتها مقارنة بنظيرتها التقليدية، وقد تم استعراض تجربة صندوق الحج الماليزي (تابونغ حاجي) باعتباره نموذجًا رائدًا في تطبيق مبادئ الحوكمة وذلك لغرض الاستفادة من تجربته، ويمكن إرجاع تميز صندوق الحج لتطبيقه السليم للحوكمة. ويُعد صندوق الحج واحدًا من أبرز المؤسسات المالية الإسلامية في ماليزيا. يهدف هذا البحث إلى إلقاء الضوء على مفهوم الحوكمة المؤسسية وأسسها ومبادئها في المؤسسات المالية الإسلامية، بعد ذلك، يناقش البحث مدى تطبيقها في صندوق الحج، وذلك بتحليل هيكلية الحوكمة كإطار توجيهي يستند إليه مجلس الإدارة في صندوق الحج، والهيكل التنظيمي لتوزيع الوظائف والأقسام والشُعَب، وإدارة المخاطر والرقابة الداخلية، وإطار الإشراف له، مع الإشارة لواقع تطبييق الحوكمة الشرعية في صندوق الحج. وقد وظّف البحث المنهج الوصفي والتحليلي، لجمع وتتبع كل ما يتعلق بالحوكمة، مع تحليل ممارسات الحوكمة بصندوق الحج. وأظهرت النتائج التي توصل إليها البحث تأكيد نجاح الصندوق في الحفاظ على مكانته البارزة ضمن المؤسسات المالية الإسلامية في ماليزيا، وذلك بفضل تبنيه لأفضل ممارسات الحوكمة وتكيفه مع التطورات المعاصرة في مجال التمويل الإسلامي والتنمية المستدامة، مما أسهم بشكل فعّال في استمراريته ونموه. Abstract This research highlights the significance of implementing governance in Islamic financial institutions, distinguished by their unique characteristics compared to their conventional counterparts. To benefit from its experience, the experience of the Malaysian Hajj Fund (Tabung Haji) was examined as an exemplary model in applying governance principles. Distinction of the Hajj Fund can be attributed to its proper governance practices. Tabung Haji is considered as one of the prominent Islamic financial institutions in Malaysia. The research aims to shed light on the concept of institutional governance, its foundations, and principles within Islamic financial institutions. The research then discusses the extent of the institutional governance application in the Hajj Fund by analysing governance structure as a guiding framework, which can rely on by the Board of Directors of the Hajj Fund. It also discusses the organizational structure for distributing jobs, departments and divisions, risk management, internal controls, and its supervision framework, regarding implementing the Sharia governance in the Hajj Fund. The research employs descriptive and analytical methods to collect and track everything related to governance, analyzing governance practices in the Hajj Fund. The results reached by the research confirmed the Fund’s success in maintaining a leading position among Islamic financial institutions in Malaysia. That is by its adherence to best governance practices and adaptation of contemporary developments in the field of Islamic finance and sustainable development. That all contributed effectively to its continuity and growth.